1990
DOI: 10.1259/0007-1285-63-751-557
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and cysteine levels in human tumour biopsies

Abstract: There is evidence that some human tumours could be treated with a combination of buthionine sulfoximine and hypoxic cell sensitizers. However, clinical application of this technique requires a prior knowledge of the level of non-protein bound sulfhydryl (NPSH) compounds in these tumours. The present study provides data on the levels of glutathione (GSH) and cysteine (CYS) in human tumour biopsies from the cervix and from the head and neck. The NPSH compounds were measured by high performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Kolanjiappan et al and Parise et al reported increasing GSH levels with tumor stage 9,10. This correlation was not found by Guichard et al6 but they limited their study to primarily T2 and T3 patients 11. Similarly, Inci et al found no difference in GSH levels when comparing patients grouped as either stage I/II or stage III 12.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Kolanjiappan et al and Parise et al reported increasing GSH levels with tumor stage 9,10. This correlation was not found by Guichard et al6 but they limited their study to primarily T2 and T3 patients 11. Similarly, Inci et al found no difference in GSH levels when comparing patients grouped as either stage I/II or stage III 12.…”
Section: Discussionmentioning
confidence: 88%
“…Two studies found no correlation between GSH levels and the degree of differentiation 6,7. However, Wong et al found higher levels of GSH in well differentiated oral carcinoma compared with moderately differentiated tumors 8.…”
Section: Discussionmentioning
confidence: 97%
“…GSH is known to be depleted in-patients exposed to carcinogen agents, such as cigarette smoke, air pollutants, occupational exposure, and viral diseases that are typically associated with cancer (3). However, elevated levels of GSH in head and neck tumors and metastatic lymphnodes were observed by Guichard et al (4). On the other hand, Peters et al (5) showed that mean value of glutathione did not differ significantly between normal, esophageal, and tumor tissues.…”
Section: Introductionmentioning
confidence: 94%
“…22 In clinical studies, GSH levels were approximately 4-fold greater in oral tumor tissue than that in the surrounding ''normal'' epithelium. [23][24][25][26] In one study, increased tumor GSH levels correlated with the stage of the disease. 25 Also, increased GSH levels have been reported in cheek pouch tumors in the DMBA-induced hamster model.…”
mentioning
confidence: 96%